2015
DOI: 10.1007/s10853-015-8931-2
|View full text |Cite
|
Sign up to set email alerts
|

Observations of fcc and hcp tantalum

Abstract: The metal tantalum has many varied uses including in microelectronics (especially in capacitors) as thin films, in medical applications as an implant material or for surgical instruments, in X-ray lithography for masks, and in high-temperature structural applications. Ta is particularly useful because it is relatively ductile, refractory in nature, and does not readily react with corrosive materials. The body-centered cubic (bcc) crystal structure of pure Ta, also known as the a-phase, is the most commonly obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…The phase transition between hexagonal-close-packed (HCP) and face-centered-cubic (FCC) structures has been well-regarded as one of the most important solid-solid phase transitions, and has raised great research interests during the past decades 1 26 . The HCP-FCC phase transition could be induced by mechanical deformation or temperature change 5 23 , and has been extensively observed in a lot of metals and alloys such as Ti 5 8 , Hf 9 , Zr 10 , Co 11 13 , Si 4 , Ta 14 , Al 15 , Au 16 , LnH 17 , MgTi 18 , TiAl 19 , TiZr 20 , CoCrMo 21 , FeMn 22 , FeMnSi 23 etc. Especially, it is reported that the HCP-FCC phase transition could bring about the shape memory effect of several alloys 19 , 25 , and the appearance of the FCC structure can improve the ductility of the metals and alloys with the HCP structure 20 , 25 .…”
Section: Introductionmentioning
confidence: 99%
“…The phase transition between hexagonal-close-packed (HCP) and face-centered-cubic (FCC) structures has been well-regarded as one of the most important solid-solid phase transitions, and has raised great research interests during the past decades 1 26 . The HCP-FCC phase transition could be induced by mechanical deformation or temperature change 5 23 , and has been extensively observed in a lot of metals and alloys such as Ti 5 8 , Hf 9 , Zr 10 , Co 11 13 , Si 4 , Ta 14 , Al 15 , Au 16 , LnH 17 , MgTi 18 , TiAl 19 , TiZr 20 , CoCrMo 21 , FeMn 22 , FeMnSi 23 etc. Especially, it is reported that the HCP-FCC phase transition could bring about the shape memory effect of several alloys 19 , 25 , and the appearance of the FCC structure can improve the ductility of the metals and alloys with the HCP structure 20 , 25 .…”
Section: Introductionmentioning
confidence: 99%
“…The SAED pattern shows the Ta precipitate to have a fcc crystal structure, 0.43 nm in the [111] direction. This is interesting, as the most common form of Ta, known as the α phase, has a bbc crystal structure, as reported by Janish et al [27], although the formation of fcc Ta structure in Ta thin films has also been reported by Denbigh et al [28]. Shen et al [29] pointed out that the small particles may exhibit lower potential energy and can become thermodynamically stable fcc crystal structures before melting.…”
Section: Annealed Specimen (Case 6)mentioning
confidence: 76%
“…The cover figure illustrates the potential for linking this type of modeling to EBSD and TEM texture studies. Indeed, TEM has revealed FCC and HCP grains (and even twinned FCC grains) existing in heavily deformed Ta [4], which is another reason for this writers interest in the selected paper.…”
mentioning
confidence: 93%